China: An unfinished reform agenda - Fan, Shenggen; Qian, Keming; Zhang, Xiaobo (International Food Policy Research Institute, 2006)
Agricultural production in China has grown rapidly—relative to other countries— over the past four decades. Much of this growth can be attributed to investments in agricultural research by national and regional governments combined with policy reform and increased use of inputs.1 After 50 years of development, the Chinese agricultural research system is now arguably the largest in the world, employing over 50,000 senior scientists and spending more than US$3.8 billion in 2002 (measured in 1995 international dollars).2 However, the system is currently facing a dilemma. Chinese agricultural production is becoming increasingly dependent on new technologies generated by research, especially as agricultural land and other natural resources become more limiting factors. The quantity of agricultural land—and high-quality land in particular—will only decline further in the future with rapid industrialization and urbanization. At the same time, a national policy introduced in the mid-1980s has encouraged research institutes to become financially self-supporting. As a result, on the positive side, research has become more integrated with economic development because research institutes have sought financial support by selling their services. On the negative side, however, areas of research not easily commercialized, including significant aspects of agricultural research, face financial problems as governments at various levels reduce funding for R&D.